Is there a Difference? The Performance Characteristics of SRI Equity Indexes - Michael Schröder (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
Investments in socially responsible investments (SRI) are still a small, but growing segment of international capital markets. This study analyses whether a SRI screening process applied to equities results in a different performance outcome compared to relevant conventional benchmark indexes. In contrast to other studies, the analysis concentrates on SRI indexes and not on investment funds. This has several advantages, which include that the transaction costs of funds, the timing activities and the skill of the fund management do not have to be considered. This leads to a relatively direct measure of the performance effects of SRI screens. The 29 SRI stock indexes are analysed by single-factor models with benchmarks that closely approximate the investment universe of the SRI stock indexes and by multi-equation systems that also exploit the information in the cross-section. The results show that SRI stock indexes do not exhibit a different risk-adjusted return than conventional benchmarks. But many SRI indexes have a higher risk relative to the benchmarks. These findings are robust to the use of different sets of benchmark indexes and apply to all common types of SRI screening.
Keywords: M14; G14; G11; 330; Socially responsible investing; equity indexes; performance; risk; Kapitalanlage; Verantwortung; Investitionsrisiko; Wertpapieranalyse; USA